Pengaruh Nickel-Chrome Plating Terhadap Kekerasan Mikro, Kekasaran Permukaan Dan Keausan Pada Hasil Produk Pengecoran Aluminium Bekas (Scrap) - Rohi, Jemssy Ronald; Bistolen, Boy; Lopo, Elkana B; Pinto, Gaspar M P; Hanmina, Marsianus M F (Badan Kerja Sama Teknik Mesin Indonesia, 2024)
In the aluminum casting process, the resulting cast product still has defects that affect the quality of mechanical properties, so it is necessary to perform the final processing by electrolysis with nickel-chromium. The aim of this research is to determine the effect of nickel-chromium coating on the results of used aluminum casting products with electrical voltages of 5, 7.5, 9 volts and times of 5, 10, 15 seconds. From the test results, it is shown that at electrical voltage of 5 and 7.5 volts with time of 5, 10, 15 seconds and at electrical voltage of 9 volts with time of 5 seconds, the hardness value is still in the nickel hardness range, while at electrical voltage of 9 volts with time of 10 and 15 seconds, it is already in the chromium hardness range. When testing the surface roughness, a decrease of 39.36% was observed after 5 seconds, a decrease of 49.70% after 10 seconds and a decrease of 63.90% after 15 seconds. These results show that the roughness level of the nickel-chromium coating is already in the surface roughness range of the finishing or final machining. The highest wear value was at 5 seconds at a voltage of 5 volts, namely 9.86E-07 mm2/kg. The lowest wear value was at 15 seconds at a voltage of 9 volts, namely 2.213E-07 mm2/kg. Therefore, nickel-chromium coating is known to increase the wear resistance of the coated material.